Evaluation of tolerance to Phytophthora cinnamomi Rands in avocado (Persea americana Miller.) germplasm - Eberto Rodriguez Henao; Álvaro Caicedo Arana; Ayda Lilia Enriquez Valencia; Jaime Eduardo Muñoz Florez (Acta Agronómica)
In order to obtain twenty-one evaluated accessions from the Avocado Germplasm Bank of CORPOICA, Palmira Research Station with two pathogenic strains of the oomycete, Phytophthora cinnamomi Rands. The aim of this research was to identify avocado accessions, which used as rootstocks in a cultural control strategy for preventing root rot disease. Disease progression was evaluated using mycelium of the pathogen by cut-stem inoculation. The measurements of symptom progression length and width were carried out and analyzed. In order to obtain the area under the disease progression curve (AUDPC), these data were analyzed. A randomized complete block design (RCBD), with a factorial design of 3 x 21 in-subdivided parcels (2 strains of the pathogen, a control strain, and 21 avocado accessions) was performed. Eight readings were determined per plant throughout evaluation time. Statistical analysis showed significantly differences using the AUDPC for some avocado accessions. Tukey's test revealed five tolerance levels. Accession ‘NATU-001’ from Tumaco, Nariño, was identified as promising for its high tolerance and ‘CANO-008’ from Norcasia, Caldas, as a tolerant control accession had the second lowest value of AUDPC. Susceptible accessions used as control, e.g. ‘Hass’ variety and rootstock ‘Topa-Topa’, performed a very high susceptibility to the pathogen along with ‘QUIQUI-030’ accession from Quimbaya, Quindío, Colombia